Production of Amylase in Liquid Culture by a Strain of Aspergillus oryzae - Kundu, A. K. (1970)
The effect of different media and pH on the formation of amylase by Aspergillus oryzae EI 212 is described. Depending upon the composition of the medium and growth conditions, the fungus was found to secrete α- or β-amylase, or both. Some of the properties of the partially purified α-amylase were found to be different from α-amylases from other sources.